All Days 2011
DOI: 10.2118/143663-ms
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Skin Factors for Perforated Completions Calculated with Computational Fluid Dynamics Software and a Semi-Analytical Model

Abstract: There are many factors affecting flow performance of perforated completions. These factors include perforation tunnel geometry, drilling and perforation damage, formation anisotropy, etc. The combined effect of these factors is usually accounted for via a single parameter – total skin factor, which is an important input parameter for Inflow Performance Relationship (IPR) prediction and reservoir simulation. The commonly used semi-analytical skin factor model assumes total skin factor can be expressed as a line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…CFD has been applied successfully in many industries and recently in the oil and gas industry. Considerable technical papers presented the application of CFD for inflow well performance, formation damage, completion design, fracturing, matrix acidizing and development of inflow control device (ICDs) [3][4][5][6][7][8][9]. This paper is using Comsol package for numerical modeling.…”
Section: Application Of Computational Fluid Dynamic (Cfd)mentioning
confidence: 99%
“…CFD has been applied successfully in many industries and recently in the oil and gas industry. Considerable technical papers presented the application of CFD for inflow well performance, formation damage, completion design, fracturing, matrix acidizing and development of inflow control device (ICDs) [3][4][5][6][7][8][9]. This paper is using Comsol package for numerical modeling.…”
Section: Application Of Computational Fluid Dynamic (Cfd)mentioning
confidence: 99%
“…Byrne et al (2011) made several simulations to capture the effect of crossflow between layers and the formation damage effect on it. Sun, et al (2011) studied with this technique the skin factor on perforated completions considering the effects of formation damagee, perforation damage and anistotropy. Sansoni et al (2007) proposed a 3D-3D model to solve the wellreservoir coupling aiming to correct predict the horizontal well productivity.…”
Section: Introductionmentioning
confidence: 99%
“…These numerical simulations culminated in the semi-analytical productivity solution developed by Karakas and Tariq (1991). Although several notable efforts were made to improve the model with numerical and analytical solutions (Dugolu, 1998;Anseh et al 2002;Yildiz, 2006;Atkinson et al 2009;Sun et al 2011), no major issues have been identified. A few discrepancies between the model and numerical simulation results were primarily because of different, usually unrealistic, assumptions used in the numerical simulations rather than defects of the semi-analytical model.…”
Section: Introductionmentioning
confidence: 99%